Transesterificación de aceite vegetal usando ceniza del residuo agroindustrial del Oenocarpus bataua como catalizador heterogéneo en Iquitos – 2022 - Del Castillo Tapullima, Mayra Denisse (2024)
The present study shows the experimental research to obtain biodiesel using ashes from the agro-industrial waste of unguarui (Oenocarpus bataua) calcined as a heterogeneous catalyst in the transesterification of used vegetable oils. The agroindustrial waste was collected from the Negocios Agroindustriales Loreto NALSAC company and the used vegetable oil was collected from the FUNDESAB facilities. The used vegetable oil was physically and chemically characterized, obtaining humidity values of 0.42% and acidity level of 0.62%. The agro-industrial residues of ungurahui (Oenocarpus bataua) were taken to the oven at a temperature of 90°C for 120 minutes to eliminate moisture, then they were pulverized, and finally they were placed in the muffle at 700°C for 4 hours, obtaining the catalyst. CRAUC. Through atomic absorption analysis, the amount of potassium (12.04%) and calcium (6.24%) were determined. The results show a maximum yield of 81.76% of biodiesel using 4% of the catalyst, alcohol/oil molar ratio 9/1 and reaction time of 120 minutes. The analysis of variance shows a p value < 0.05 for a significance level α=0.05, indicating significant differences in the biodiesel yields obtained in the different reaction trials. The presence of the ester functional group was confirmed by mid infrared spectroscopy analysis with a maximum value of 98.7% V of methyl ester in the produced biodiesel. It was concluded that agroindustrial waste from unguarui (Oenocarpus bataua) has great potential to be used as heterogeneous catalysts in the transesterification reaction of used vegetable oils, due to the presence of potassium and calcium in its chemical composition.